Synthesis and Antifungal Potential of Co(II), Ni(II) and Cu(II) Chelates with Nitrogen, Oxygen and Sulphur Containing Schiff Bases - Rai, Rajeshwar; Baluni, Akhilesh; Kumari, Poonam; Rai, B.K. (Asian Journal of Chemistry, 2015)
In the present article a series of complex of the type ML2 where M = Co(II), Ni(II) and Cu(II), L = 2-butyl-[3-hydroxy propyl)-3,1-(4H)-quinazoline semicarbazone/thiosemicarbozone have been synthesized. Their structures were confirmed by means of molar mass, elemental analyses, infrared spectra, electronic spectra, magnetic susceptibility and conductivity measurement. All the compounds were screened against species of plant pathogenic fungi using disc diffusion technique. It was observed on comparison with reference to fungicides, the complexes were found to be more effective than ligands,